Damped harmonic signals analysis using ADZT - Kubak, Jan (International Society for Science and Engineering, o.s., 2020)
This article discusses analysis of damped harmonic signals by spectral methods, ApproximatedDiscrete Zolotarev Transform (ADZT) in particular. The ADZT behavior for this type ofsignal is explored, and tailored method modification is proposed. It is shown that the modificationperforms better compared to the discrete Fourier transform and selected parametric spectral methodsin detection of partially masked damped harmonic signal components.